Multiplex families with epilepsy: Success of clinical and molecular genetic characterization. (23rd February 2016) - Afawi, Zaid; Oliver, Karen L.; Kivity, Sara; Mazarib, Aziz; Blatt, Ilan; Neufeld, Miriam Y.; Helbig, Katherine L.; Goldberg-Stern, Hadassa; Misk, Adel J.; Straussberg, Rachel; Walid, Simri; Mahajnah, Muhammad; et al.
Abstract : Objective: To analyze the clinical syndromes and inheritance patterns of multiplex families with epilepsy toward the ultimate aim of uncovering the underlying molecular genetic basis. Methods: Following the referral of families with 2 or more relatives with epilepsy, individuals were classified into epilepsy syndromes. Families were classified into syndromes where at least 2 family members had a specific diagnosis. Pedigrees were analyzed and molecular genetic studies were performed as appropriate. Results: A total of 211 families were ascertained over an 11-year period in Israel. A total of 169 were classified into broad familial epilepsy syndrome groups: 61 generalized, 22 focal, 24 febrile seizure syndromes, 33 special syndromes, and 29 mixed. A total of 42 families remained unclassified. Pathogenic variants were identified in 49/211 families (23%). The majority were found in established epilepsy genes (e.g., SCN1A, KCNQ2, CSTB ), but in 11 families, this cohort contributed to the initial discovery (e.g., KCNT1, PCDH19, TBC1D24 ). We expand the phenotypic spectrum of established epilepsy genes by reporting a familial LAMC3 homozygous variant, where the predominant phenotype was epilepsy with myoclonic-atonic seizures, and a pathogenic SCN1A variant in a family where in 5 siblings the phenotype was broadly consistent with Dravet syndrome, a disorder that usually occurs sporadically. Conclusion: A total of 80% of families were successfully classified, with pathogenic variants identified in 23%. The successful characterization of familial electroclinical and inheritance patterns has highlighted the value of studying multiplex families and their contribution towards uncovering the genetic basis of the epilepsies.